The changing nature of the workplace and the future of office space. Issue 5 (3rd August 2015) - Harris, Rob
Abstract : Purpose: – The purpose of this paper is to outline key changes happening within occupier businesses that will have a medium- to long-term impact upon the demand for office space and, ultimately, the property investment market. Design/methodology/approach: – The paper is based on survey work undertaken for the City of London Corporation as well as direct experience in advising corporate occupiers on their accommodation needs. Findings: – The findings suggest major changes taking place in the demand profile of office occupiers, in terms of both quantitative and qualitative demand for space. Practical implications: – There are a number of practical implications arising from the findings, not the least being the need for investors to consider the appropriateness of current standards for base building design and fit-out in contemporary offices. Originality/value: – The paper presents the output of primary research and consulting and is therefore of an original nature. Its value lies in the fact that the findings reflect the actual experiences and plans of corporate occupiers and can be taken as reliable indicators of future demand for office space.